Family friendly policies and work-life balanced organisations / David McCullough and Tony Proctor (Faculty of Business and Management ; UiTM Press, 2006)
Early in 2000 the UK Government launched its Work Life Balance campaign. The campaign was intended to raise employer's awareness of the business benefits of introducing policies and practices which help employees obtain a better work life balance. Central to the campaign is a belief that everyone benefits from good practice in work life balance. This paper concerns research undertaken in the Legal Services of a Council to answer the question whether family friendly policies really benefit all concerned. The research methodology utilised a questionnaire, focus groups, individual interviews, an examination of available documentation and an analysis of the state of the organization compared with the Investors in People model of a work-life balanced organisation.